Recurrent Focal Myositis of the Left Thigh– rare but treatable inflammatory myopathy - A case report - Wahinuddin Sulaiman; Eskandar @ Zulkarnain Hassan (Asian Journal of Medicine & Health Sciences, 2018)
Focal myositis presents as an acute and localized inflammation of the muscle without systemic involvement. The etiology is unknown. Several case reports in the literature have described different presentations of the condition, the majority affecting the limbs with a spectrum of clinical progression, laboratory, and radiological findings. It is often confused with infection, muscle tumor such as sarcoma, paraneoplastic syndrome or even immune-mediated polymyositis. Delay in diagnosis and inappropriate treatment may lead to recurrence of the condition. We report a case of recurrent focal myositis of the left thigh in a man in whom optimal treatment commenced six months after the onset led to regression of his symptoms and signs.